Racial and Cultural Tension in Lorraine Hansberry’s A Raisin in the Sun - Neupane, Dipesh (Cognition, 2022)
The culture in which we are brought up shapes our traits and identity. When people move from one place to another, they get acquainted with new cultures. Then, they vacillate on the conflicting modes of dilemma – whether to follow the new culture or not. Cultural conflict arises when people cannot discard the original culture they carry from their birth. This paper explores how an African-American family confronts racial discrimination and culture clash in America, and how they react against the racial injustice. The voices that African-America people raise against racial discrimination and segregation are overtly or covertly represented in the African-American literature, as in the play- “A Raisin in the Sun”. This study explores the conflict between American culture and African culture in the play conceptualizing the theoretical frame work of cultural studies developed by Geert Hofstede and Edward Hall. This study answers the question: how does the African-American family (Younger family) confront the culture clash, and combat against racial discrimination in the play? The conflict between the Younger family and the white representative indicates the racial and culture clash between the African and the America culture as dramatized in the play.